Dynamic characteristics and hazard analysis of the high-altitude landslide based on multi-source data and numerical simulation - Gao, Jingxuan; Cui, Xueliang; Zhang, Nan; Wang, Lichao; Wang, Wenpei; Li, Yuanyuan (Frontiers in Earth Science, 2025)
The Bailong River Basin is located on the eastern edge of the Qinghai-Tibet Plateau, where tectonic activities are intense and the geological environment is complex. It is one of the high-incidence areas of high-altitude landslides in China. A total of 316 potential geohazards were identified in the Zhouqu region using the InSAR technique, and their spatial distribution exhibits a clear correlation with regional fault structures. Taking the Lijie landslide as the study subject, this research comprehensively employs high-resolution optical remote sensing, Unmanned Aerial Vehicle (UAV) aerial surveys, in-situ monitoring, and numerical simulation techniques to achieve multi-scale, multi-temporal, and three-dimensional monitoring of the landslide, as well as quantitative simulations of its stability and dynamic evolution process. For the significantly deformed A1 and A2 blocks in the Lijie landslide, GNSS and deep displacement monitoring revealed their spatio-temporal deformation characteristics. Numerical simulation indicated that the two deformed blocks were in a critical unstable state under natural conditions (with safety factors of 0.959 and 0.916 respectively), and would easily transform into debris flows after instability, posing a serious threat to the residents and towns downstream. This study established a landslide hazard assessment system from identification, monitoring to simulation prediction, providing a scientific basis for geological hazards assessment in strong tectonic zones.